THE IDEAS OF VISUAL LEARNING IN THE PEDAGOGICAL HERITAGE OF ABDULLA AVLONI AND THEIR ADAPTATION TO MODERN INTERACTIVE MEDIA TECHNOLOGIES IN PRESCHOOL EDUCATIONAL ORGANIZATIONS - Djurakulova Lola Rakhmonovna; Bushevskaya Karina Eduardovna (International Journal of Literature and Language Studies, 2026)
The article examines the historical and pedagogical legacy of the prominent Uzbek Jadid enlightener, Abdulla Avloni, through the prism of the challenges posed by the modern information society and the digitalization of preschool education. Based on a comparative analysis, the authors draw a parallel between the classical Jadid principle of visual learning (implemented in new-method textbooks of the early 20th century) and contemporary practices of gamification in preschool educational organizations. The study systematizes and theoretically substantiates three distinct representational patterns of knowledge visualization: the transformation of plot-based modeling (from fables to web quests), the evolution of didactic feedback (from the mentor's approval to instant digital animation), and structural-functional mapping. It is demonstrated that the controlled implementation of interactive media technologies across accessible educational platforms enhances the cognitive activity of senior preschoolers, provided they are strictly integrated with traditional productive activities and comply with the national hygienic regulations of the Republic of Uzbekistan (SanPiN).